Pulmonary microlithiasis: A case of forensic autopsy and a brief literature review - Gelsomina Mansueto; Emanuele Capasso; Massimo Niola; Mariano Paternoster (Elsevier, 2018)
Background: Pulmonary alveolar microlithiasis (PAM) is a rare autosomal recessive disease with a high penetrance characterized by widespread intra-alveolar accumulation of countless minute calculi called microliths. Patients with PAM may be asymptomatic, and the diagnosis is often an accidental finding during medical imaging performed for other diseases. Otherwise, it can develop into pulmonary fibrosis. In both cases, the disease can lead to respiratory and pulmonary heart failure which, though occurring rarely, may have a fatal outcome. Case presentation: We report the case of a 40-year-old male found dead in the bathroom. In the absence of trauma or other signs of injuries and in absence of a history of previous diseases, forensic autopsy was required to identify the time, cause and means of death. Our final diagnosis was death by right ventricular hypertrophy with initial signs of acute ischemia in a patient with PAM. Conclusions: This case provides insights into a pathology which is not frequent and can lead to death, besides illustrating the importance of histology in solving cases that come within a forensic setting. Therefore histology is fundamental to diagnose the cause of death, supplemented by knowledge of physiology and pathology in the cardiovascular and respiratory. Keywords: PAM, Alveolar microlithiasis, Forensic autopsy, Pulmonary hypertension